2021
DOI: 10.3389/fimmu.2021.757827
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Microenvironment During Kingella kingae Infection Modulates Osteoclastogenesis

Abstract: Kingella kingae is an emerging pathogen that causes septic arthritis, osteomyelitis, and bacteremia in children from 6 to 48 months of age. The presence of bacteria within or near the bone is associated with an inflammatory process that results in osteolysis, but the underlying pathogenic mechanisms involved are largely unknown. To determine the link between K. kingae and bone loss, we have assessed whether infection per se or through the genesis of a pro-inflammatory microenvironment can promote osteoclastoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Intriguingly, BEVs counteracted bacteria-mediated osteoclastogenic pathways. For example, K. kingae OMVs decreased osteoclastogenesis in a dose-dependent manner and inhibited proinflammatory cytokine production by infected macrophages ( Pesce Viglietti et al, 2021 ). Therefore, BEVs exhibit advantages in bone health, and these studies offer a mechanistic basis for BEV-mediated osteoprotective functions.…”
Section: Physiological and Pathological Roles Of Bevs In Specific Sys...mentioning
confidence: 99%
“…Intriguingly, BEVs counteracted bacteria-mediated osteoclastogenic pathways. For example, K. kingae OMVs decreased osteoclastogenesis in a dose-dependent manner and inhibited proinflammatory cytokine production by infected macrophages ( Pesce Viglietti et al, 2021 ). Therefore, BEVs exhibit advantages in bone health, and these studies offer a mechanistic basis for BEV-mediated osteoprotective functions.…”
Section: Physiological and Pathological Roles Of Bevs In Specific Sys...mentioning
confidence: 99%
“…Infection disrupts this reciprocal balance, enhancing bone resorption and slowing bone formation, but the underlying mechanisms are unclear 15 . For instance, James et al demonstrated that infection triggered osteoblast death, and Ayelén et al showed that infection modulated osteoclastogenesis; both of these outcomes are detrimental to bone healing 11,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The rtxA gene is absent in other Kingella species except K. negevensis ( 26 30 ). RtxA is cytotoxic against a broad range of eukaryotic cells in vitro , including red blood cells, epithelial cells (HeLa, A549, FaDu, HLac-78), endothelial cells, synovial cells (SW-982, Hig-82), osteoblasts (U-2), and monocytes (THP-1, RAW264.7) ( 18 , 24 , 31 33 ). Mutants that lack RtxA are non-hemolytic and non-cytotoxic in vitro and are avirulent in an infant rat model of invasive disease, underscoring the role of this toxin as a major contributor to K. kingae virulence ( 10 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond secretion via the TISS, RtxA is released from the organism in outer membrane vesicles (OMV). OMV production is highly variable among clinical isolates ( 31 , 32 ). Along with RtxA, K. kingae OMVs contain a host of other proteins in the outer membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation